Faktor-faktor yang mempengaruhi kebijakan dividen pada perusahaan non keuangan - NOVIA WIJAYA (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to analyze the factors affecting on dividend policy of non financial company that listed in Indonesian Stock Exchange for period 2011 until 2013. This research use return on equity (ROE), current ratio (CR), debt to equity ratio (DER), sales growth (SG), investment opportunity set (IOS), size of firm (SIZE), and total asset turnover (TATO). The data are collected from 99 non financial company listed at Indonesian Stock Exchange (BEI) and the observation period are three years. Sampling method used is purposive sampling and data analysis with multiple linear regression. Empirical evidence shows that, sales growth has influence to dividend policy and return on equity, current ratio, debt to equity ratio, investment, size firm, and total asset turnover have not influence to dividend policy.